Integration Between Religion and Science in Islamic Studies in Integrated Islamic Junior High School - Asmaldi, Asmaldi; Husti, Ilyas; Zamsiswaya, Zamsiswaya; Syafril, Syafrimen (Khalifa Journal of Islamic Education, 2022)
This study aims to analyze how the integration of Islam and science in Islamic Religious Education subjects at the Integrated Islamic Junior High School in Batam City so far and to find out a model of the integration of religion and science in Islamic Religious Education subjects that are relevant to the context of the Integrated Islamic Junior High School in Batam City. To answer the research questions, the research approach used is a qualitative approach. Research data were collected using observation, interviews, and documentation. The collected data is then analyzed using a qualitative approach. The results of the analysis show that first, there has been no integration of religion and science in Islamic Religious Education subjects at the Integrated Islamic Junior High School in Batam City so far. Second, based on field data and analysis of the relevant literature, the researcher found a model of the integration of religion and science in Islamic Religious Education subjects that was relevant to the context of the Integrated Islamic Junior High School in Batam City. The model in question is a Two-Way Thematic model. With the design of this integration model based on problems and needs in the field as well as relevant theories, this model is considered capable of being a solution for the unimplemented integration of religion and science in Islamic Religious Education subjects at the Integrated Islamic High School in Batam City.